A STUDY ON INCOME DISTRIBUTION AND SOCIO-ECONOMIC CONDITIONS OF MGNREGA HOUSEHOLDS - Muneeswaran, P.; Sundarapandian, C. (International Journal of Research -GRANTHAALAYAH, 2021)
The Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA) 2005 is one of the foremost social security in India. It guarantees minimum wage, reduces poverty and checks large scale migration in rural India. It has reduced rural hunger. After implementation of MGNREGA, the Planning Commission estimated that the poverty among Scheduled Castes () in rural areas fell 22 percentage points- from 53.5 per cent in 2004-05 to 31.5 per cent in 2011-12. For that reason, the study focuses on income distribution and the conditions of MGNREGA workers and their households in district of Tamil state. The sample size of this research work is 345 MGNREGA Scheduled Castes () workers. The study found that there is a significant level of association existing between the annual income of MGNREGA workers/households and their conditions, such as the participants’ gender, age, community and occupation, type of family, size of family, number of employees and migrant workers of the family in the study area.At the same time this study found that there is no significant level association existing between annual income and conditions such as education, type of houses, and marital status. Hence, the MGNREGA is one of themajor factors in determining the income level and also the conditions of the of scheduled castes workers in the study area.